Hubungan Pola Asuh, Pemberian Makanan dan Pengetahuan Ibu Terhadap Kejadian Stunting pada Balita di Wilayah Kerja Puskesmas Sungai Guntung Kecamatan Kateman Kabupaten Indragiri Hilir Tahun 2024 - Devianty, Mellina Shilla; Septiani, Winda; Gumayesty, Yeyen (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
The purpose of this study was to determine the relationship between parenting patterns, feeding, and maternal knowledge with the incidence of stunting in toddlers in the working area of Puskesmas Sungai Guntung Kateman District, Indragiri Hilir Regency. The research method used in this study was quantitative analytic with a case-control study design. The population in the study were mothers who have toddlers aged 24-59 months. Respondents in this study numbered 106 respondents, who were taken using a purposive sampling technique. Data analysis used univariate and bivariate. The results of the study concluded that there was a significant relationship between maternal parenting patterns, feeding, and maternal knowledge with the incidence of stunting in toddlers in the working area of Puskesmas Sungai Guntung Kateman District, Indragiri Hilir Regency.